Up-cycling of 'unrecyclable' glasses in glass-based foams by weak alkali-activation, gel casting and low-temperature sintering. (1st January 2021) - Ramteke, Durgaprasad D.; Hujova, Miroslava; Kraxner, Jozef; Galusek, Dušan; Romero, Acacio Rincón; Falcone, Roberto; Bernardo, Enrico
Abstract: A significant amount of glasses is landfilled because mainstream recycling solutions do not address the articles of specific chemical compositions, including opal glass and glass fibers residues. This manuscript suggests the up-cycling of these glasses through the production of highly porous glass foams. Fine glass powders were dispersed in weakly alkaline solutions, which were foamed by the combination of surfactant addition and intensive mechanical stirring. The cellular structures were stabilized first by the gelation of suspensions, upon drying, then by viscous flow sintering at 700–800 °C, for 10–60 min. The foams based on glass fibers reached an excellent strength-to-density ratio, due to the formation of closed cells and partial crystallization. The foams made from opal glass maintained a particularly uniform open porosity, and importantly, also retained the volatile and toxic fluorine due to the rapid, low-temperature sintering. Highlights: Unrecyclable glasses of large industrial interest, glass fibres and opal glass, were upcycled to glass foams. Foams from glass fibres demonstrated an excellent strength-to-density ratio. Opal glass based foams showed an excellent uniform open porosity. Fluorine from original waste glass was fully retained in the new material. In both cases time and energy consumption were reduced to minimum.